Peran Pekerja Sosial dalam Pelayanan Paliatif: Studi Kasus di Instalasi Paliatif dan Bebas Nyeri RSUD Dr. Soetomo Surabaya - Pairan Pairan; Misnia Septa Andiana (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
Indonesia is currently experiencing a parallel epidemiological transition, the epidemiological transition can be marked by a change in the pattern of death which is dominated by non-communicable diseases. To overcome this phenomenon, palliative care is needed by the hospital. Palliative care is interdisciplinary and multi-professional care. One of the professions required in palliative service is the profession of social work. This is in appropriate with the Decree of the Minister of Health of the Republic of Indonesia No.812 / Menkes / SK / VII / 2007. Palliative service consists of service stages, namely administrative, medical and non-medical services. Administrative services are handled by the hospital administration department, medical services are carried out by the medical team, while non-medical services are handled by psychologists, volunteers and social workers. This study has a purpose to describe the role of social workers in palliative services. This research use desciptive qualitative approach. In determining the location using the purposive area technique and the determination of informants using purposive sampling technique. Data collection was carried out by interview, observation and documentation. The data analysis technique was performed using the Miles and Huberman model which was carried out through data accumulate, data reduction, conclusions and verification. The results showed that the role of social workers needed in palliative services is the role of providing social support to patients and their families, helping patients and families to overcome financial problems, and playing a role in restoring social functioning of patients. The role in providing social support can be seen from how social workers also assist patients and their families and provide awareness of the importance of family roles for patients. The role in overcoming economic problems is to become a broker between patients and funding aid agencies. The role in restoring the patient's function is by providing motivation, understanding, and strengthening to the patient that he is valuable and very meaningful to his family and providing knowledge to the patient's family so that he continues to provide opportunities for patients to play a role socially according to the patient's condition.